Praktikum Pemanfaatan dan Pengolahan Daun Cincau Hijau (Cyclea Barbata) Mata Pelajaran IPAS Kelas V di Mi Jami’yatul Mubtadi’in - Ika Dini Akmalia; Muhammad Suwignyo Prayogo; Sindi Wulandari (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Green grass jelly (Cyclea barbata) leaves are one of the herbal plants found in Indonesia and have various potential health benefits. This plant is known to contain bioactive compounds such as flavonoids, tannins, and alkaloids that act as antioxidants, anti-inflammatories, and help regulate blood sugar levels in the body. The utilization of green grass jelly leaves is not only as a refreshing traditional drink ingredient, but also as a source of natural medicine that is environmentally friendly and easily accessible to the community.This activity aims to increase awareness and knowledge of students and teachers about the benefits of green grass jelly leaves, as well as teach simple but effective processing techniques to produce value-added processed products.The research method used descriptive qualitative method.The results of this activity showed an increase in participants' understanding and skills in processing green grass jelly leaves into products that are suitable for consumption, as well as fostering interest in utilizing herbal plants as part of a healthy lifestyle.